Genetic variability following selection for scrapie resistance in six autochthonous sheep breeds in the province of Bolzano (northern Italy). (21st April 2020) - Bordin, Fulvio; Dalvit, Chiara; Caldon, Mauro; Zulian, Laura; Colamonico, Rosa; Trincanato, Simone; Mock, Barbara; Reale, Stefano; Mutinelli, Franco; Granato, Anna
Abstract: Scrapie is an ovine transmissible spongiform encephalopathy, and its susceptibility is associated with polymorphisms in the prion protein gene ( PRNP ). Genetic selection is currently the most effective mean for eradication of the susceptible VRQ allele in favour of resistant ARR allele. Maintenance of genetic diversity should be one of the major objectives in breeding programmes, especially in endangered breeds, and genetic information are an excellent alternative to pedigree data where these information are missing. The aim of our study was to determine changes of genetic variability in six native sheep breeds from autonomous province of Bolzano, northern Italy, following simulation of scrapie selection scenarios. A total of 684 rams were investigated for PRNP polymorphisms and for 10 microsatellite loci to estimate genetic variability. Across all loci, a total of 163 alleles were detected with a mean of 10.4 alleles per locus. Average observed (Ho) and unbiased expected (uHe) heterozygosity overall loci were 0.74 and 0.78, respectively, showing a statistically significant deviation from Hardy–Weinberg equilibrium (HWE) in all breeds. This heterozygosity deficit was confirmed by a positive fixation index (Fis), determining a moderate inbreeding in each breed. Simulating a soft selection, where only rams having at least a VRQ allele should be excluded from reproduction, Ho, uHe and Fis values remained almost unchanged, indicating that genetic variability should not be affected by the removal of these individuals. With a mild selection scenario, considering only rams with at least one ARR allele, we observed a decrease in the mean alleles per breed (8.9) and the maintenance of heterozygosity deficiency, except for two breeds, where it was any longer significant. These results showed that selection strategies allowing use of heterozygous as well homozygous ARR rams might be the right compromise to improve resistance to scrapie and to do not dramatically affect genetic variability of these breeds.